Reactive Oxygen Species (ROS) in Living Cells - Filip, Cristiana; Albu, Elena (IntechOpen, 2018)
Oxygen represents only 20% of the Earth's atmosphere, yet it is vital for the survival of aerobic organisms. There is a dark part of the use of oxygen that consists in generating reactive species that are potentially harmful to living organisms. Moreover, reactive oxygen species can combine with nitrogen derivatives and generate many other reactive species. Thus, living organisms are continuously assaulted by reactive species from external or internal sources. However, the real danger comes in the case of high concentrations and prolonged exposure to these species. This book presents an image of the mechanisms of action of reactive species and emphasizes their involvement in diseases. Inflammation and cancer are examined to determine when and how reactive species turn the evolution of a benign process to a malignant one. Some answers may come from recent studies indicating that reactive species are responsible for epigenetic changes.